Influência do forro de gesso acartonado no isolamento ao ruído de impacto de sistemas de pisos de laje com vigotas protendidas e lajotas cerâmicas - Santos, Eduardo Henrique Lucca (2020)
The discomfort related to impact noise in residential building floor systems is a common problem in multifamily buildings and is a source of inconvenience to users of buildings. In this context, it is necessary to study the acoustic performance of different configurations of floor systems, in order to provide scientific basis for the comparison between the materials available on the market. The present study seeks to analyse the acoustic performance regarding impact noise of a prefabricated slab with prestressed joists and ceramic blocks, adopting as a solution the use of plasterboard ceiling. Tests were carried out to determine the weighted standardized impact sound pressure level (L’nT,w) of different floor system configurations. The tests followed the requirements of ISO 16283-2 (2018) and the treatment of the data followed the procedures described in ISO 717-2 (2013). The classification of the level of performance of the floor systems was made based on the values of L’nT,w established in ABNT NBR 15575-3 (2013). Two ceiling systems were used: ceiling with plasterboard (150 mm plenum) and ceiling with plasterboard and a 50 mm PET wool insulation (150 mm plenum). Various configurations of floor systems containing the ceilings described, ceramic floors, vinyl floors, laminate wood flooring and resilient materials were tested. The suspended ceiling technique is an efficient solution for impact noise reduction in floor systems with prefabricated slabs, being an alternative to the floating floor technique. For the floor system with plasterboard ceiling (150 mm plenum) installed under the prefabricated slab, a 74 dB L’nT,w was found, meaning an improvement in the insulation to impact noise equal to 17 dB in relation to the L’nT,w of the slab without the plasterboard ceiling. Also, the ceiling technique can be used together with the floating floor technique, in situations where a higher level of performance is desired for floors that separate dwellings. The efficiency of the suspended ceiling solution depends on the type of floor used, being more efficient for systems with ceramic or vinyl floors than for systems with laminate wood flooring. The efficiency of the suspended ceiling solution also depends on the impact noise insulation provided by the other layers of the floor system, the greater the insulation provided by the system without the ceiling, the less efficient the installation of the false ceiling is to insulate impact noise. Furthermore, the placement of the 50 mm PET wool insulation between the plasterboard and the slab can provide an improvement of up to 3 dB in the insulation to the impact noise of the floor system, depending on the materials of the other layers of the system. It was noted that the placement of fibrous sound absorbing material in the plenum is a solution to the insulation of impact noise at low frequencies (below 125 Hz).